2020
DOI: 10.3233/wor-203227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of carpal tunnel syndrome symptoms among Iranian butchers and their association with occupational risk factors: Implications for ergonomic interventions

Abstract: BACKGROUND: Carpal tunnel syndrome (CTS) is a common disorder among occupations where upper extremities are actively involved in. Many occupational and non-occupational risk factors may contribute to this disorder. Knowledge regarding occupational risk factors can guide us to implement interventional programs. OBJECTIVE: The aim of the present study was to assess the prevalence and severity of CTS symptoms among butchers and their association with several occupational and non-occupational risk factors. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Also, several studies have demonstrated various predisposing elements, including individual and occupational factors (3)(4)(5). Specific occupations and physical exposures, for instance, typists, tailors, butchers, housekeepers, and hairdressers or, in an overall view, manually performed jobs with extensive grip and vibration exposure, are stimulators of CTS (6)(7)(8)(9)(10). factors of CTS, as only 10% of CTS reported cases are under 30 years old, and also it affects women three times more than men between 45 and 60 years of age (11).…”
Section: Introductionmentioning
confidence: 99%
“…Also, several studies have demonstrated various predisposing elements, including individual and occupational factors (3)(4)(5). Specific occupations and physical exposures, for instance, typists, tailors, butchers, housekeepers, and hairdressers or, in an overall view, manually performed jobs with extensive grip and vibration exposure, are stimulators of CTS (6)(7)(8)(9)(10). factors of CTS, as only 10% of CTS reported cases are under 30 years old, and also it affects women three times more than men between 45 and 60 years of age (11).…”
Section: Introductionmentioning
confidence: 99%
“…M. Musolin & Ramsey, 2017;Palmer, 2011;Spahn, Wollny, Hartmann, Schiele, & Hofmann, 2012). Hal ini terjadi akibat saraf medianus pada pergelangan tangan tejepit oleh pembungkus tendon fleksor yang menebal, tulang terikat, dan edema/massa jaringan lunak (Ghasemi, Gholamizadeh, Rahmani, & Doosti-Irani, 2020; K. M. Musolin & Ramsey, 2017).…”
unclassified